Pelatihan Daring Pertolongan Pertama Psikologis Penyintas Bencana pada Dharma Wanita Persatuan Kota Bogor - Riastuti Kusuma Wardani; Ratri Ciptaningtyas (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Natural disasters, especially landslides, often occur in Bogor City because naturally the contours of the area are at risk of landslides. Dharma Wanita as a social organization can be a driving force for aid when a disaster occurs. However, there has never been any training on disaster response knowledge and skills, especially Psychology First Aid (PFA). PFA training aims to provide capacity knowledge and skills to members of Dharma Wanita to help disaster survivors. The training was delivered through online for 1.5 hours for material on understanding PFA, the purpose and importance of PFA, implementing PFA, stages and methods of PFA, the second 2 hours of practice on the stages and methods of PFA, and evaluating for 30 minutes with question-and-answer quizzes. After that, an offline follow-up was carried out to visit the affected areas. The result, based on the training evaluation, the selected participants were able to explain the questions correctly. Participants were also enthusiastic about following up the training by visiting survivors in disaster-affected areas. However, this training did not measure the participants' PFA skills because this training was carried out after the disaster occurred, so this training did not prepare for landslides at that time.